1987
DOI: 10.1029/rg025i005p00833
|View full text |Cite
|
Sign up to set email alerts
|

Planetary geodesy

Abstract: This report will attempt to review progress in planetary geodesy during the past four years. We basically restrict the discussion to gravity, topography, rotation and their physical significance. The format has been kept flexible to accommodate the varied amount of information available for the different planets. The bibliography provided is representative but not exhaustive. In addition to previous quadrennial reports by Kaula [1975], Anderson [1975], Ferrari and Bills [1979], and Sjogren [1983], publications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1988
1988
1998
1998

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 81 publications
0
4
0
Order By: Relevance
“…In order to compare with other researcher's results, using the six-layer lunar model constructed by Bills and Ferrari (1977) (simplified as BF-6) we completed also the same computation. For the model BF-6 the algorithm used in the determination of the values of p(r), Vp(r) and Vs(r) is based on a cubic spline.…”
Section: The Calculated Results Of the Love Numbersmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to compare with other researcher's results, using the six-layer lunar model constructed by Bills and Ferrari (1977) (simplified as BF-6) we completed also the same computation. For the model BF-6 the algorithm used in the determination of the values of p(r), Vp(r) and Vs(r) is based on a cubic spline.…”
Section: The Calculated Results Of the Love Numbersmentioning
confidence: 99%
“…Due to recent achievements in planetary geodesy, at present important geodetic parameters of these planets are provided with high accuracy (e.g., Bills and Synnott, 1987). The geodetic parameters of the terrestrial planets and the Moon adopted in this study can be found in Table II.…”
Section: The Parametric Models Of the Internal Structure For The Moonmentioning
confidence: 99%
See 1 more Smart Citation
“…I note at the outset that the determination of such cartographically significant but essentially astronomical values as the rotation period and axis orientation, and the definition of cardinal directions and prime meridians, are outside the scope of this paper. The procedures are fully documented in the astronomical literature (e.g., Davies et al 1986Davies et al , 1994; a useful review is given by Bills and Synnott 1987).…”
mentioning
confidence: 99%